2009
DOI: 10.1097/hjh.0b013e32831101d1
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain, a circulating hormone secreted by the adrenals, is pivotal in cardiovascular disease. Fact or fantasy?

Abstract: Substantial evidence points to the presence in human plasma of an inhibitor of the sodium/potassium pump which plays a central role in the pathophysiology of circulatory disorders, including essential hypertension. Studies from the 1980/90s claimed that this inhibitor was identical or very similar in structure to plant-derived ouabain and was synthesized by the adrenal cortex. However, the physical evidence in studies reporting isolation and identification of ouabain in human plasma appears insecure on closer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 56 publications
2
43
0
Order By: Relevance
“…On the other hand, release of adrenal cortical hormones during WD could also modulate activity of the sympathetic nervous system centrally and/or peripherally. The adrenocortical hormones corticosterone (47)(48)(49)(50)64), aldosterone (1,23,24,27,29), and endogenous oubain (2,5,35,36,40) all have the ability to influence SNA and affect arterial pressure. Additional studies are required to determine the role of these hormones in the regulation of arterial pressure during WD.…”
Section: Role Of the Adrenal Gland In The Regulation Of Arterial Presmentioning
confidence: 99%
“…On the other hand, release of adrenal cortical hormones during WD could also modulate activity of the sympathetic nervous system centrally and/or peripherally. The adrenocortical hormones corticosterone (47)(48)(49)(50)64), aldosterone (1,23,24,27,29), and endogenous oubain (2,5,35,36,40) all have the ability to influence SNA and affect arterial pressure. Additional studies are required to determine the role of these hormones in the regulation of arterial pressure during WD.…”
Section: Role Of the Adrenal Gland In The Regulation Of Arterial Presmentioning
confidence: 99%
“…Plant-derived cardiotonic steroids contain a five-membered lactone ring while the cardiotonic steroids of animal origin contain a six-membered lactone ring (Schoner & Scheiner-Bobis 2005). In humans, one cardiotonic steroid isolated from adrenal glands and plasma appears to be identical to plant-derived ouabain by NMR and mass spectroscopy (Nicholls et al 2009) and is designated as EO.…”
Section: Introductionmentioning
confidence: 99%
“…As ouabain has been found in human plasma (6, 9, 19 -20, 25-28) and identified as a human hormone (21,26), information regarding other activities of this compound is of great interest and will benefit both physiological and pathological knowledge. Although some studies have reported the apoptotic induction property of ouabain in cancer cells (4,11,23,35), the molecular basis of this induction and the precise role of this compound in TRAILmediated cancer cell death are not known.…”
mentioning
confidence: 99%